2015
DOI: 10.1088/0960-1317/26/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

A capacitor-based sensor and a contact lens sensing system for intraocular pressure monitoring

Abstract: This study proposes a capacitor-based sensor on a soft contact lens for the measurement of intraocular pressure (IOP). The sensor was designed and fabricated via microelectromechanical system fabrication technologies. The soft contact lens is designed to be worn on a cornea such that the curvature of the contact lens corresponds substantially to that of the cornea. In addition, the contact lens was fabricated via a cast-molding method using poly-2-hydroxyethyl methacrylate to achieve a lens with high oxygen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
24
0
1
Order By: Relevance
“…Extant studies [ 7 , 8 ] presented the design and fabrication of an IOP capacitive sensor. Figure 4 shows the principle and fabrication process of the IOP capacitive sensor.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant studies [ 7 , 8 ] presented the design and fabrication of an IOP capacitive sensor. Figure 4 shows the principle and fabrication process of the IOP capacitive sensor.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies demonstrated a microelectromechanical system (MEMS) capacitive pressure sensor on a contact lens [ 7 , 8 ] and sensor chips [ 9 , 10 ] for long-term IOP monitoring. An extant study demonstrated the wireless harvesting of smart contact lens and antenna design [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Using the miniaturization advantages of microelectromechanical systems (MEMS) technology and microfluidics systems, new implantable IOP sensors can be developed for continuous IOP monitoring. The upcoming sensors can be implanted in the anterior chamber,[ 10 11 12 13 14 ] embedded intraocularly or in a contact,[ 15 16 17 18 19 20 21 22 ] or integrated into a tonometry device for better measurement accuracy. [ 23 ] Currently, some continuous pressure monitoring systems such as Triggerfish ® (Sensimed AG, Switzerland) and EYEMATE ® (Implandata Ophthalmic Products GmbH, Germany) have been used in clinical applications, but further development or the availability of an optimal implantable IOP sensor are necessary before these systems can be used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…(4) By 1957, the applanation tonometer designed by Goldmann, had become an important IOP assessment tool because of its ability to perform accurate and reliable measurements. (4) The use of the Goldmann tonometer is thus considered the standard measurement technique for glaucoma. However, this device is not suitable for the real-time measurement of the IOP, as it is not portable or wearable.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of this device is 1.2239 pF/mmHg for pressures between 18 and 30 mmHg. (4) Because of its complex structure, it is difficult to achieve mass production and its practical application is limited. Ghaed et al developed a cubicmillimeter energy-autonomous wireless IOP monitor.…”
Section: Introductionmentioning
confidence: 99%